Mediterranean lifestyle patterns are associated with cognition in older adults - Eirini Mamalaki; Dimitrios Poulimeneas; Mary H. Kosmidis; Mary Yannakoulia (Wiley, 2021)
Abstract Introduction In recent years, research interest has shifted to the study of overall lifestyle, rather than individual lifestyle factors, in relation to health outcomes. The aim of this study was to investigate the association of different lifestyle patterns, close to the concept of the Mediterranean lifestyle, using both a priori and a posteriori methods, with cognition of older adults, free of dementia. Methods A total of 1726 participants ≥65 years old (59% women) from the HELIAD study were included in the present cross‐sectional analysis. Diet, physical activity, sleep, social life, and daily functioning were assessed using standard, validated questionnaires. A comprehensive neurological and neuropsychological assessment was conducted, evaluating all cognitive domains: memory, executive functions, visual-spatial perception, language, and attention‐processing speed, as well as global cognitive functioning. Results Two lifestyle indices were constructed on the basis of the Mediterranean lifestyle, whereas principal component analysis was used to generate lifestyle patterns. The results showed that the two indices and the Mediterranean diet and activities pattern as well as the Mediterranean diet and social contacts pattern were positively associated with almost all major cognitive domains as well as global cognitive functioning. Specifically, every unit increase in one of the lifestyle indices, consisting of adherence to the Mediterranean diet, sleep quality, physical activity, and daily functioning, was associated with 9.8%, 7.1%, 6.8%, 7.2%, and 8.5% increased odds of better memory, executive function, visual-spatial perception, language, and global cognitive functioning, respectively. Conclusions Our results showed that a healthy lifestyle, close to the concept of the Mediterranean lifestyle, independently of the approach used to define it, was positively associated with cognitive function in older adults. Thus, health experts should also consider overall lifestyle when screening for cognitive deficits in this vulnerable age group.